(untitled) (International journal of medical sciences, 2026)
Forensic medicine constitutes a vital component of the criminal justice system by providing scientific medical evaluations for legal purposes. The conclusions of forensic medical experts frequently influence court decisions and investigative outcomes. Nevertheless, inaccuracies and professional errors in forensic practice may result in severe legal, ethical, and societal repercussions. This article examines the principal forms of errors encountered in forensic medicine, identifies the factors contributing to their reminder, and analyzes their potential consequences for judicial processes. Furthermore, effective approaches to reducing forensic errors are discussed, with particular attention given to professional training, methodological rigor, and institutional oversight.